Personalisasi Konten dan Pengaruhnya terhadap Minat Pelanggan Kota Medan di Marketplace Tiktok - Fitriana, Dhea; Sikumbang, Ahmad Thamrin (Riwayat: Educational Journal of History and Humanities, 2025)
Customers on TikTok Marketplace, with a specific focus on the context of Medan City. The rapid development of digital technology has fundamentally transformed consumer behavior, where social media particularly TikTok has now become a primary platform for people to search for product information and make purchasing decisions. Through the use of advanced algorithms, TikTok is able to present content that is personally tailored to individual user preferences, thereby significantly increasing relevance and engagement. Content personalization has proven to offer a variety of strategic benefits in marketing, including enhanced brand awareness and equity, driving word-of-mouth marketing, increasing customer lifetime value, and optimizing the return on investment (ROI) of marketing campaigns. These benefits highlight the importance of personalization in building strong and sustainable customer relationships. Although personalization offers great potential to boost purchase intention and customer loyalty, this study also identifies potential challenges related to the "filter bubble." The amplification of content that aligns too closely with user interests may risk reducing content diversity, thus limiting users exploration of new topics and potentially affecting trust. Therefore, it is essential for businesses to balance relevance with content diversity. By understanding local consumer preferences and managing personalization strategically, businesses can develop more effective marketing strategies, increase purchase intentions, and achieve sustainable business success on digital platforms.